The Immediate Feedback Assessment Technique: A Learner-centered Multiple-choice Response Form - DiBattista, David (Canadian Journal of Higher Education, 2013)
The Immediate Feedback Assessment Technique (IFAT) is a new multiple-choice response form that has advantages over more commonly used response techniques. The IFAT, which is commercially available at reasonable cost and can be used conveniently with large classes, has an answer-until-correct format that provides students with immediate, corrective, item-by-item feedback. Advantages of this learner-centered response form are that it: (a) actively promotes learning; (b) allows students’ partial knowledge to be rewarded with partial credit; (c) is strongly preferred by students over other response techniques; and (d) lets instructors more easily maintain the security of multiple choice (MC) items so that they can be reused from one semester to the next. The IFAT’s major shortcoming is that grading must be done manually because it does not yet have a compatible optical scanning device. Helpful suggestions are presented for instructors who may be considering using the IFAT for the first time. RÉSUMÉ La Technique D’Évaluation Immédiat (Immediate Feedback Assessment Technique ou IFAT) est un nouveau formulaire pour examens à choix multiple qui a plusieurs avantages. Le IFAT, disponible à un prix raisonable et convenable pour les cours suivis par de nombreux étudiants, est constitué d’un format dans lequel les édudiants selectionnent alternative-par- alternative parmi les choix disponibles jusqu’à ce que la réponse correcte soit indiquée. En suite, la correction est automatique et informe la réponse correcte immédiatement. Le IFAT a plusieurs avantages: (a) il favorise l’apprentissage; (b) les étudiants peuvent obtenir des points partiels avec connaissances partiels; (c) les étudiants préferent ce formulaire à comparer à autres formats à choix multiple; et (d) les instructeurs peuvent maintenir plus facilement leurs questions et alternatives en sécurité et les réutiliser au cours des prochaines sessions. Le défaut principal du IFAT est que la notation est manuele car il n’y a pas encore de lecteur optique compatible avec ce formulaire. Des suggestions utiles sont ici données pour les instructeurs qui envisagent d’utiliser cette technique pour la première fois.